An indissoluble knot: An unexpected troubleshooting during Micra implantation. Issue 6 (27th December 2018) - Cipolletta, Laura; Volpato, Giovanni; Biffi, Mauro; Capucci, Alessandro
Abstract: Micra is a transcatheter leadless pacing system delivered percutaneously through femoral vein access into the right ventricle. We are going to describe an initially standard procedure, with an unexpected troubleshooting at the end: the impossibility to release the device and retract the delivery due to a knot in the tether.